Transformasi UKM: Faktor Eksternal dan Adopsi Inovasi Lingkungan dengan Lingkungan Ramah Lingkungan sebagai Mediasi di Kota Batu: Transformasi UKM, Faktor Eksternal, Adopsi Inovasi Lingkungan, Lingkungan, UKM - Luh Dina Ekasari, Luh; Dwi Sasono, Agus (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This study examines the external factors driving the transformation of Small and Medium Enterprises (SMEs) in Batu City, with a focus on the role of environmentally friendly innovations as a mediator. Adapting to a changing business environment and external challenges is essential for SME survival, especially in the context of global environmental sustainability. The research uses quantitative methods, including surveys to assess external influences and the adoption of environmental innovations among Batu City SMEs, and in-depth interviews to explore SMEs' attitudes toward these practices. Data analysis identifies significant external factors, such as government policies, market conditions, competition, financial resources, and infrastructure, which influence the adoption of environmentally friendly practices. The findings reveal that these practices enhance SMEs' environmental sustainability and play a critical role in their transformation. Additionally, the study highlights that external factors and environmental innovations significantly impact SME transformation, both directly and through the mediation of an environmentally friendly environment. The results emphasize the need for SMEs to integrate environmental considerations into their business strategies to ensure sustainable transformation and long-term success.